The Importance of E-Learning as a Tool for Independent Learners in Higher Education and Technical Colleges - Mukhtorov Alisher Mukhtorovich (International Journal on Integrated Education, 2021)
The article highlights the importance of effective use of independent working hours using a variety of methods and tools to acquire excellent knowledge and skills in existing disciplines in higher education institutions and technical schools. It is also important to develop teaching aids, methods and recommendations that take into account the individual abilities and scientific characteristics of students in the organization of independent work, their application in practice, the development of cooperation between related and different institutions, the use of resources of advanced enterprises is suspended.